NOSIR FOZILOV ESSELARINING BADIIY-MA’RIFIY XUSUSIYATLARI - Matchanov, S. (SCIENCE and SOCIETY, 2024)
In this article, the essays of the children’s writer Nasir Fazilov are analyzed. Information about the life of Nasir Fazilov in the article helps the reader to understand the works of the writer.